2000
DOI: 10.1128/aem.66.1.268-276.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Bacteriological Population Changes through Potable Water Treatment and Distribution

Abstract: This pilot study compares the compositions of bacterial biofilms in pipe networks supplied with water containing either high levels of biodegradable organic matter (BOM) or low levels of BOM (conventionally or biologically treated, respectively). The Microbial Identification System for fatty acid analysis was utilized in this study to identify a large number of organisms (>1,400) to determine population changes in both conventionally and biologically treated water and biofilms. Data generated during this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(142 citation statements)
references
References 27 publications
11
121
1
9
Order By: Relevance
“…The bar represents 1 % sequence divergence DWDs (Lu et al 2013). Moreover, the composition of the bacterial community in chlorinated (or chloraminated) water might be much different from that in non-chlorinated (or non-chloraminated) water (Norton and LeChevallier 2000;Berry et al 2006;Eichler et al 2006;Kormas et al 2010;Poitelon et al 2010). Unfortunately, very few research works have provided the phylogenetic description of bacterial community in the sand filter effluent and the BAC filter effluent.…”
Section: Bacterial Community Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The bar represents 1 % sequence divergence DWDs (Lu et al 2013). Moreover, the composition of the bacterial community in chlorinated (or chloraminated) water might be much different from that in non-chlorinated (or non-chloraminated) water (Norton and LeChevallier 2000;Berry et al 2006;Eichler et al 2006;Kormas et al 2010;Poitelon et al 2010). Unfortunately, very few research works have provided the phylogenetic description of bacterial community in the sand filter effluent and the BAC filter effluent.…”
Section: Bacterial Community Structuresmentioning
confidence: 99%
“…It is generally accepted that chlorination can result in a dramatic shift in the composition of the bacterial community (Norton and LeChevallier 2000;Eichler et al 2006;Kormas et al 2010;Poitelon et al 2010), yet little information is available on the bacterial community change through other drinking water treatment units. Pinto et al (2012) found that filtration by dual media rapid sand filters in a drinking water plant played a primary role in shaping the bacterial community in DWDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Acidovorax spp. are frequently detected in water-distribution systems in developed countries (Norton & LeChevallier, 2000;Williams et al, 2004), and Acinetobacter spp., Dietzia maris and Bacillus spp. are commonly found in soil and in lakes.…”
Section: Technical Limitationsmentioning
confidence: 99%
“…Mycobacteria of MAC have the capacity to survive and multiply under a wide range [128] and low oxygen level [16]. Thus, their ability to utilise many substances as nutrients enables them to grow successfully in many biotopes.…”
Section: Physiological Characteristics For Environmental Survivalmentioning
confidence: 99%